Konstrukcja znamion typu rodzajowego przestępstwa wypadku komunikacyjnego – uwagi krytyczne - Jurewicz, Justyna (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
The article contains the overview of problems connected with interpretations of elements of offence described in art. 177 Polish Penal Code. The essence of the text shows the difficulties that are shaped on the practical side of circumstances in traffic. The theses which can be found in the text are shown through the opinions of Polish courts and doctrine. This article gives a cause to think over once again the sense of the elements of the offence in relation to the sense of features of other road transport offences.